Effect of floor type on the growth performance and health status of growing-finishing pigs - Garcimartin, M.A.=700 1 Ovejero, I.; Vazquez Minguela, J.; Daza, A.
(En, Es)
Ilus., 18 ref.
Keywords: CERDO; CRECIMIENTO; CONSUMO DE AGUA; OLOR; PRODUCTIVIDAD; SANIDAD ANIMAL; SUELO; RESINAS; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH